Academic professional development : a case study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Education at Massey University - Au, Wing Kee (Massey University, 1983)
The major objective of this investigation was to study the academic professional development of staff members (N = 34) from a department of a New Zealand university. To achieve this objective, a case study approach to data collection was adopted. This involved interviews with the staff members, and consulting documents relating to professional development at the university in which the study was carried out. As well, people involved with academic professional development at the universities throughout New Zealand and overseas were consulted. Seven major themes emerged from this study. The themes are: Induction into the Department, The Roles of Academic Staff Members, Attitudes towards Professional Responsibilities, Role Improvement, The Evaluative Procedures, The Reward System, and Ways of Professioanl Development. Among the major findings were : - structured assistance for academic staff during their first six months in the department being investigated was non-existent; the roles of the academic staff in this department included teaching, research, administration, work in the community and other (e.g. communicating with colleagues); the most and least satisfying aspects of their role for academic staff members were teaching and administration respectively; formal or systematic opportunities for professioanl development of the academic staff members did not exist; formal evaluation of the professional responsibilities of academic staff was not carried out; and the formal reward system in the department emphasised promotion through research and publication. On the basis of these findings, two major recommendations were suggested for the professional development of these academic staff members : (1) A systematic induction programme for those staff members new to the department, especially those who have not previously held an academic appointment and those who have had no previous association with the department; and (2) More opportunities should be provided for those staff members who wish to improve their professional skills and competencies, particularly in the area of teaching and research. Such opportunities could be provided by setting up workshops and seminars and by encouraging the formation of interest groups within the department. This investigation also attempted to contribute to the study of academic professional deveopment by focussing upon a theoretical framework based on role theory. A model which highlights the nomothetic and idiographic factors influencing the roles of academics has been presented.
Keywords: Academic professional development; New Zealand universities